2012
DOI: 10.1089/neu.2011.2008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT Improves Outcome Prediction in Acute Traumatic Brain Injury

Abstract: The admission noncontrast head computed tomography (CT) scan has been demonstrated to be one of several key early clinical and imaging features in the challenging problem of prediction of long-term outcome after acute traumatic brain injury (TBI). In this study, we employ two novel approaches to the problem of imaging classification and outcome prediction in acute TBI. First, we employ the novel technique of quantitative CT (qCT) image analysis to provide more objective, reproducible measures of the abnormal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Increased precision in characterizing regional pathophysiology will enable more objective control of injury type and severity in order to distill the specific mechanism by which ANKK1 modulates working memory, as a subset of the disparate patterns of cognitive impairment observed in the current TBI classification system of mild, moderate and severe. In a broader sense, further development of classification approaches based on quantitative morphometry [70], in conjunction with appropriate computational methods [71] and data integration processes [72], will aid in deconstructing the contribution of genetic modulation to multidimensional domains of outcome after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Increased precision in characterizing regional pathophysiology will enable more objective control of injury type and severity in order to distill the specific mechanism by which ANKK1 modulates working memory, as a subset of the disparate patterns of cognitive impairment observed in the current TBI classification system of mild, moderate and severe. In a broader sense, further development of classification approaches based on quantitative morphometry [70], in conjunction with appropriate computational methods [71] and data integration processes [72], will aid in deconstructing the contribution of genetic modulation to multidimensional domains of outcome after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…If the images from the initial CT examinations of those eight subjects share a similar density distribution with the rest of the severe edema subjects, the early detection of cerebral edema would be possible. The basis for this assumption is that the initial non-enhanced brain CT images possess significant prognostic value regarding TBI [47]. Tests on subjects revealed that HU 24 17 was able to differentiate the two groups successfully (Figures 4 and 6).…”
Section: Cerebral Edema Scorementioning
confidence: 98%
“…Quantitative CT (QCT) methods have beeen mainly used in other specialties, such as cardiology and pulmonology [36][37][38][39][40][41][42][43]. Recent neuroradiological studies, which used densitometry analysis, focused on finding tumors or regional pathological changes [44][45][46][47][48]. Only a handful of studies used densitometric methods for whole brain images of abnormal brains [49][50][51][52].…”
Section: Technical Implicationsmentioning
confidence: 99%
“…Yuh et al [12] studied the correlation between quantified radiographical features and GOS score, as well as the correlation between the major components and GOS score after principle component analysis (PCA). The study focused more the interdependence of the features rather than GOS prediction.…”
Section: Related Workmentioning
confidence: 99%